Building a National Commitment Against Hoax Threats for Indonesian Sovereignty - Sri Widiastutik; Anak Agung Surya Pradhana; I Gusti Agung Istri Aryani (Catuspata, 2022)
This research initiated to offer a strong commitment to defend the sovereignty of Indonesia. The purpose of this research to advise and create awareness of each people to commit and must be wise in receiving and disseminating information, especially hoax. This research used the literature study method by analyzing the impact that has been caused by hoaxes. In collected the data, the author’s team searched, listed, and displayed the main data and the supported data as the most fake news in social media. The author classified the data into two, are the main data was accessed from the Minister of Communication and Informatics news, even was completed by the supported data that were listed from the news posted on declared hoaxes as a common enemy that destroys the order of life in Indonesia. The data have been collected by the case studies were easily influencing people’s opinions and even could be potentially disrupt the national security of our nation. The result of the research in order to produce an important reference that educate the public to deal with hoaxes. This research initiated to offer a wise solution for face hoax through collected the data have been listed by literature study and analyzed the impacts for our society in Indonesia. In digital literacy, people need to know the characteristics of hoaxes so as not to get caught up with fake news, or slander that is circulating. This fake news will certainly harm many parties, including you. For that, be wise in reading, analyzing, and trusting information, before you disseminate it.